Implementasi Sistem Bagi Hasil (Paron) antara Nelayan dan Pemilik Bagan di Kelurahan Kolo Bima dalam Perspektif Syariah - Rizkullah, Ahmad; Muslimin, H.; Sirajuddin, Sirajuddin (AHKAM, 2024)
The fishermen still face numerous challenges in implementing the Islamic profit-sharing system. The urgency of this research is crucial, as the implementation of this profit-sharing system ensures that the agreed-upon plans between the fishermen and the boat owners have either negative or positive impacts on the agreed-upon profit-sharing system. Most fishermen are dissatisfied with the profit outcomes that do not align with the initially agreed-upon terms. The research methodology employed in this study is phenomenology, a method that utilizes life experiences as a tool to better understand the socio-cultural, political, or historical context in which those experiences occur. This research will discuss a subject by understanding the core experiences of a phenomenon that takes place. Additionally, supplementary data such as documentation and others regarding the implementation of the profit-sharing system between boat owners and fishermen will be included. The research is conducted in the village of Kolo, Asakota Bima District. The location is situated in the coastal area, serving as the fish landing base for the fishermen. Moreover, the presence of boat owners is in close proximity to the fishermen, sharing the same location. The profit-sharing system between boat owners and fishermen in the community of Kolo, Asakota Bima District, is carried out through the paron system or the two-share system. This means that the expenses for vessel management, such as engines and nets, are borne by the boat owner, while the crew's wages are covered by the fishermen. The resulting profits are then divided, with one part going to the capital owner and the other to the fishermen, commonly known as a 1/2 sharing ratio.